Enhanced anaerobic co-digestion of food waste and solid poultry slaughterhouse waste using fixed bed digester : Performance and energy recovery - Ahmad, Anwar; Ghufran, Rumana; Nasir, Qazi; Shahitha, Fathima; Al-Sibani, Mohammed; Al-Rahbi, Amal (Elsevier B.V., 2023)
This study investigated the effects of organic loading rate (OLR) for anaerobic co-digestion (AcoD) of food waste (FW) and solid poultry slaughterhouse waste (SPSW) was performed in a fixed bed digester (FBD) at controlled pH to improve the methane production not fully discovered. Anaerobic co-digestion FW and SPSW were started up for the first time by gradually increasing OLR. At steady state, the FBD-AcoD reactor at OLR of 23.5 g COD/L/d the methane production was 7.8 L/L/d. Which achieved the highest OLR of 23.5 g COD/L, on the other hand when at OLR of 25.5 to 27.5 g COD/L the digester appeared inhibited and showed low performance in methane yields due to the accumulation of volatile fatty acids (VFAs) and long chain fatty acids (LCFAs). Methanosaeta and Methanosarcina were dominant over the acidogenic in the digester boosting the FBD-AcoD system to counter the acid effect. The removals of TS and VS around 79% and 76% on a continuous basis with a waste mixing of SPSW 18.5% and OLR of up to 23.5 g COD/L could biogas production 81 g COD/L/d. The FBD-AcoD system produces bioenergy of 875.3 Kj/g COD and the total investment energy utilized in the system was 8.51 Kj/g COD respectively.